1997
DOI: 10.1017/s0022112097006940
|View full text |Cite
|
Sign up to set email alerts
|

On the shape of flames under strong acoustic forcing: a mean flow controlled by an oscillating flow

Abstract: A conical flame, in the presence of high-frequency (≈1000 Hz) and high-amplitude acoustic modulation of the cold gases, deforms to a shape which is approximately hemispherical. It is shown that the acoustic level required to produce a hemispherical flame is such that the ratio of acoustic velocity to laminar combustion velocity is about 3. This flame flattening is equivalent to the phenomenon of acoustic restabilization observed for cellular flames propagating in tubes. The transition betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The effect of the confinement on the changes in the time-averaged shape of the flame by way of shrinking/elongation, tilting, and liftoff, is examined in the presence of external excitation over a frequency range of 400-800 Hz at acoustic velocity amplitudes that are comparable to or less than the mean flow velocity at the inlet. The contrast in the frequency and amplitude ranges where these features are observed when compared to those where similar features are observed in the previous studies with open flames [14][15][16] is reported here. The role of vortex rollup, shedding, convection, and accumulation in the hot-product jet downstream of the flame and its spread and tilt in the duct under the influence of the external excitation, as suggested by many studies on nonreacting excited jets [17][18][19][20][21][22][23][24][25][26][27][28], on the oscillatory behavior of the flame such as fluctuation of its anchor points is investigated.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The effect of the confinement on the changes in the time-averaged shape of the flame by way of shrinking/elongation, tilting, and liftoff, is examined in the presence of external excitation over a frequency range of 400-800 Hz at acoustic velocity amplitudes that are comparable to or less than the mean flow velocity at the inlet. The contrast in the frequency and amplitude ranges where these features are observed when compared to those where similar features are observed in the previous studies with open flames [14][15][16] is reported here. The role of vortex rollup, shedding, convection, and accumulation in the hot-product jet downstream of the flame and its spread and tilt in the duct under the influence of the external excitation, as suggested by many studies on nonreacting excited jets [17][18][19][20][21][22][23][24][25][26][27][28], on the oscillatory behavior of the flame such as fluctuation of its anchor points is investigated.…”
Section: Introductionsupporting
confidence: 62%
“…The chaotic flame occurs for high-amplitude excitation in the 100-600 Hz range. Durox et al [15,16] studied the collapsed and hemispherical flames exhibited at high amplitudes of excitation in the high-frequency range (>600 Hz). A significant change in the mean shape of the flame from being conical to hemispherical or bulb-shaped is observed, which further degenerates into a structure corresponding to cellular instability at higher forcing levels.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the minimum level of the inception of the nonlinear flame response decreases with increasing modulation frequency [6,22]. Several factors affect nonlinear flame dynamics: unsteady flame liftoff [23,24], local/global extinction [23,25], equivalence ratio oscillation [26], and shear layer rollup [4,5,22]. Because an understanding of a combustor's nonlinear dynamics is critical to the prediction of the limit-cycle oscillation amplitude and nonlinear processes of mode switching and instability triggering, the nonlinear response of turbulent premixed flames has been examined.…”
Section: Flame Transfer Function Measurementmentioning
confidence: 99%
“…At 2 dρ − dp = 0 along the characteristic with the speed u ρcdu + dp = 0 along the characteristic with the speed u + c (6) ρcdu − dp = 0 along the characteristic with the speed u − c leads to the linear algebraic system (third picture in Fig. 5)…”
Section: Characteristic Based Approximate Riemann Solvermentioning
confidence: 99%
“…The interaction of acoustic waves with a Bunsen flame was suggested by Professor G. Searby [6,26]. At the same time we wanted to check whether the scheme with the RHR solver remains stable for this unsteady 2D computation.…”
Section: Oscillating Bunsen Flamementioning
confidence: 99%